Copolymerization of Limonene - Zhang, Yujie (Université d'Ottawa / University of Ottawa, 2014)
In this thesis, we explored the use of a renewable resource to produce more sustainable polymeric materials. Limonene, a monocyclic terpene existing in many essential oils extracted from citrus rinds, was the renewable monomer investigated. The d-limonene ((+)-limonene) isomer is a major component (~90%) of orange oils from orange juicing and peel processing. Having been used as a flavour and fragrance additive in cosmetics, foods and beverages, as well as a green solvent, limonene is of particular interest in polymerization, because it contains double bonds, which provide the bifunctionality necessary for polymerization. Limonene is also an allylic monomer (CH2=CH-CH2Y), which presents challenges in free-radical homopolymerization and thus, copolymerization was investigated herein to overcome this difficulty. 2-Ethylhexyl acrylate (EHA) and n-butyl methacrylate (BMA) were used in two separate projects, as comonomers with limonene. Using bulk free-radical copolymerization at 80℃, with benzoyl peroxide (BPO) as the initiator, high molecular weight (>100,000) EHA/limonene and BMA/limonene copolymers were produced. Reactivity ratios, important parameters used in the prediction of copolymer composition, were estimated and shown to accurately predict the copolymer composition of subsequent experiments. These can now be used for the application of appropriate semi-batch policies to further enhance limonene incorporation into the copolymers.
Keywords: limonene; Free-radical polymerization; Degradative chain transfer